Analisis Pengaruh Jumlah Beban Pencemaran Air antara Air Permukaan Upstream dan Downstream Kali Baru Menggunakan Metode Regresi Linear - Okik Hendriyanto Cahyonugroho; Anidah H Triwulandari (Prosiding ESEC, 2023)
The total upstream surface water pollutant load has a lower value than the total downstream surface water pollutant load. Water flows from upstream to downstream which causes changes in water quality, therefore a study was conducted with the aim of knowing the effect of the amount of upstream surface water pollutant load on the amount of downstream surface water pollutant load in Kali Baru, South Jakarta. The analysis was conducted using a simple linear regression method with the predictor variable being the upstream surface water pollutant load (X) and the response variable being the downstream surface water pollutant load (Y). The results show a constant value (a) of 0.374 while the slope value (b) is 1.022 so that the regression model Y = 0.374 + 1.022 X is obtained. From the data it can be concluded that the amount of upstream surface water pollutant load has an influence on the amount of downstream surface water pollutant load of 0.374%, while 1.022% and the rest are influenced by external variables. Both variables have a strong relationship. The influence of the two variables is that if the amount of pollutant load entering the upstream surface water body increases, the amount of downstream surface water pollutant load will also increase.